FMRI investigation of working memory in adolescents with surgically treated congenital heart disease. Issue 1 (2nd January 2017) - King, Tricia Z.; Smith, Kristen M.; Burns, Thomas G.; Sun, Binjian; Shin, Jaemin; Jones, Richard A.; Drossner, David; Mahle, William T.
ABSTRACT: Adolescents and young adults with surgically treated congenital heart disease (CHD) have been shown to exhibit difficulties with executive functions; however, the neural underpinnings of these impairments have not been previously examined with functional magnetic resonance imaging (fMRI). The current study employed fMRI to examine the neural mechanisms during a letter n-back task of working memory compared to vigilance. Seventeen participants with CHD ( M age  = 17.76 ± 1.72 years; 88% Caucasian; 30% female; mean IQ = 104.12 ± 15.15) were compared to 17 controls ( M age  = 18.40 ± 1.74 years; 70% Caucasian; 30% female; mean IQ = 110.59 ± 5.28) with similar declining performance as the n-back became more challenging. Overall, both groups activated similar frontal-parietal working-memory networks as seen in previous literature; however, some significant differences were detected between the groups. Specifically, the participants with CHD demonstrated differences within the left precuneus and the right inferior frontal gyrus. Secondary analyses indicated that this difference appeared to be due to less task-induced deactivation (TID) in the CHD group during working memory and greater working-memory TID in the control group. In CHD, prefrontal fMRI deactivation on working-memory tasks correlated with improved working-memory performance. Future complementary neuroimaging research with functional connectivity is warranted to further examine the neural underpinnings of disrupted executive function in the long-term outcomes of CHD.